ELEMEN EKONOMI DALAM PERADABAN ISLAM MASA KLASIK SEBAGAI PEMBELAJARAN PENTING UNTUK MEMBANGUN PERADABAN ISLAM MASA DEPAN - Aip Aly Arfan (DIRASAT: Jurnal Studi Islam dan Peradaban, 2018)
This research is a library research, exploring how the economic development of Islam in the time of prophet Muhammad (may peace be upon him!) and khulafāurrāsyidīn actually became the basis of economic development in the time of the Umayyads and the Abbasids and even modern Islamic civilization